The interplay between employer branding and place in the Swedish IT sector : Potential employees' perceptions of place as part of the employer value proposition - Gracia, Janine (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2023)
Purpose: To explore the interplay between employer branding and place within the Swedish IT sector. To answer the purpose of the study, two research questions have been developed. RQ1: What are IT university students’ perceptions of IT companies employer value proposition (EVP) and to what extent does place play a role in these perceptions? RQ2: How do IT companies use (or not use) place as a part of their EVP to attract potential employees? Methodology: To conduct the study, a qualitative research approach with an exploratory focus in form of semi-structured interviews were used. Six IT students from Luleå University of Technology were interviewed to explore answers related to RQ1, and three IT companies established in Luleå were interviewed to find answers for RQ2. Results: For RQ1, the result showed that the students were attracted to soft values at a potential employer. The place played a major role in the choice of employer as the respondents believe that it directly affects the connection to the place in their daily lives, in terms of well-being, the environment and proximity to family. For RQ2, the result showed that IT companies see the value of students and Luleå as an attractive place to be in and pushes the advantages of the place as a growing city and their respective company’s contribution to local development. Theoretical implications: The study explores the interplay between employer branding (EB) and place, using frameworks related to external employer branding (EEB) value propositions and place attachment (PA). It provides new insights into how students perceive EVP, and the role place has in their choice of employer and that attachment must be built for students to want to stay in the city after graduation. Practical implications: IT companies should emphasize the value in why employees should choose them over another employer, and not just communicate general descriptions about the company image. Efforts are required from the local community to increase the attachment of students and the ...